Prehension synergies - Zatsiorsky, V. M.; Latash, M. L. (Exercise and Sport Sciences Reviews, 2004)
The precision grip requires the control of the normal and tangential forces exerted by the fingers as well as the control of the rotational equilibrium of the grasped object. Prehension synergies involve the conjoint changes in finger forces and moments during multifinger gripping tasks. Some of these adjustments are dictated by mechanics, whereas others are the result of a choice by the performer. SUMMARY Control of prehension is organized in a hierarchical fashion. Tangential digit forces can contribute more than 50% to the total torque and, hence, cannot be neglected. The forces and moments at the digit tips are defined by a linear superposition of at least two commands, one command to assure stable grasping and the second one to regulate the orientation of the object. A local change in the output of an elemental variable leads to chain effects, that is, a sequence of changes in other elemental variables. Some of the observed relations among the elemental variables are mechanically necessitated, whereas others involve choice made by the controller. Finger forces during prehension are affected by finger interdependence (enslaving). In particular, the antagonist moments in part are the result of enslaving effects; strong commands to agonist fingers also activate antagonist fingers.